2016
DOI: 10.1161/circep.115.003582
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Ripple Mapping in Atrial Tachycardias

Abstract: Background-Post ablation atrial tachycardias are characterized by low-voltage signals that challenge current mapping methods. Ripple mapping (RM) displays every electrogram deflection as a bar moving from the cardiac surface, resulting in the impression of propagating wavefronts when a series of bars move consecutively. RM displays fractionated signals in their entirety thereby helping to identify propagating activation in low-voltage areas from nonconducting tissue. We prospectively used RM to study tachycard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Map consistency display was used to search for, and filter points whose LAT values are not consistent with the LAT values of neighboring points to highlight these outliers. The interpolation threshold of the color fill‐in of the reconstruction was set at 5% during map acquisition to permit a relatively uniform density of mapping points 15 . Bipolar electrograms were filtered between 16 and 500 Hz, unipolar electrograms between 2 and 240 Hz and recorded digitally 7 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Map consistency display was used to search for, and filter points whose LAT values are not consistent with the LAT values of neighboring points to highlight these outliers. The interpolation threshold of the color fill‐in of the reconstruction was set at 5% during map acquisition to permit a relatively uniform density of mapping points 15 . Bipolar electrograms were filtered between 16 and 500 Hz, unipolar electrograms between 2 and 240 Hz and recorded digitally 7 .…”
Section: Methodsmentioning
confidence: 99%
“…SNO zones were the result of the coherent mapping algorithm, exhibit absence of conduction velocity vectors on coherent map, and appear as brown on the 3D maps (Figure 1A). 15 For optimal performance, the following were likewise adjusted. Scar settings were defined with a voltage cutoff of less than 0.05 and less than 0.5 mV used to define scar and low voltage zones, respectively 16 …”
Section: Methodsmentioning
confidence: 99%
“…6,7 RM is incorporated into CARTO3v4 (Biosense Webster) and has been Ripple Mapping in Post-Infarct VT applied prospectively to guide atrial tachycardia ablation in the scarred atrium. 8 We have previously described how RM is able to visualize conducting channels of electrogram activation within scar using an offline system in a retrospective series of ventricular substrate maps. 9 This showed that pacing sites with good pace maps and where entrainment mapping confirmed participation in VT colocated with the identified ripple mapping conducting channels (RMCCs).…”
mentioning
confidence: 99%
“…9,10 We described active tissue thresholding, which helps to define the critical isthmus sites supporting re-entry as a target for ablation: by superimposing ripple activation on a bipolar voltage display, areas without any visible ripple activation can be inferred to be scar and colour-coded red on a voltage map. 11 An example of this is illustrated in Figure 3 for mapping an organised AT in an atrium with previous extensive ablation for AF, where the local activation colour sequence is uninterpretable.…”
Section: Ripple Mapping In Atrial Tachycardiamentioning
confidence: 99%
“…However, we have found that simultaneous display of the bipolar EGM voltage is helpful in interpretation of ripple map activation, particularly when understanding arrhythmia mechanisms and their relation to scarred substrates. 11,12 RM has been incorporated into a commercially available electroanatomic mapping system, CARTO ® 3 (Biosense Webster), so it can be used to guide ablation at the time of mapping. In the following sections we will review our experience of RM in elucidating the mechanisms of tachycardia within atrial and ventricular scar.…”
mentioning
confidence: 99%